Distinct preoptic‐BST nuclei dissociate paternal and infanticidal behavior in mice. (30th September 2015) - Tsuneoka, Yousuke; Tokita, Kenichi; Yoshihara, Chihiro; Amano, Taiju; Esposito, Gianluca; Huang, Arthur J; Yu, Lily MY; Odaka, Yuri; Shinozuka, Kazutaka; McHugh, Thomas J; Kuroda, Kumi O
Abstract: Paternal behavior is not innate but arises through social experience. After mating and becoming fathers, male mice change their behavior toward pups from infanticide to paternal care. However, the precise brain areas and circuit mechanisms connecting these social behaviors are largely unknown. Here we demonstrated that the c‐Fos expression pattern in the four nuclei of the preoptic‐bed nuclei of stria terminalis (BST) region could robustly discriminate five kinds of previous social behavior of male mice (parenting, infanticide, mating, inter‐male aggression, solitary control). Specifically, neuronal activation in the central part of the medial preoptic area (cMPOA) and rhomboid nucleus of the BST (BSTrh) retroactively detected paternal and infanticidal motivation with more than 95% accuracy. Moreover, cMPOA lesions switched behavior in fathers from paternal to infanticidal, while BSTrh lesions inhibited infanticide in virgin males. The projections from cMPOA to BSTrh were largely GABAergic. Optogenetic or pharmacogenetic activation of cMPOA attenuated infanticide in virgin males. Taken together, this study identifies the preoptic‐BST nuclei underlying social motivations in male mice and reveals unexpected complexity in the circuit connecting these nuclei. Synopsis: Depending on mating status, male mice show paternal nurturing or aggression toward infant mice. The authors could predict and manipulate the balance of paternal versus aggressive behavior based on neural activity in the forebrain nuclei cMPOA and BSTrh. Virgin male males are aggressive to pups while fathers show paternal nurturing. Neuronal activation patterns in two forebrain nuclei, cMPOA and BSTrh, predict paternal and aggressive behavior in male mice with 97% fidelity. Parental care requires the cMPOA, while pup‐directed aggression is facilitated by the BSTrh. A cMPOA to BSTrh inhibitory projection may mediate the behavioral switch from aggression to parenting. Abstract : Depending on mating status, male mice show paternal nurturing or aggression toward infant mice. The balance of paternal versus aggressive behavior is based on neural activity in the forebrain nuclei cMPOA and BSTrh.